Kemampuan Kognitif dan Kemandirian Belajar Siswa Menggunakan Pendekatan Kontekstual dengan Pendekatan Saintifik - Basarudin, Basarudin; Asmara, Adi; Hartati, Merri Sri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the differences in cognitive abilities and learning independence of students taught using contextual, scientific, and conventional approaches. This study used a quasi-experimental method with a Non-Equivalent Pretest–Posttest Control Group Design. The results showed that the contextual and scientific approaches significantly improved students' cognitive abilities compared to the conventional approach. The contextual approach resulted in the highest level of learning independence at 83.87%, followed by the scientific approach at 79.17%, while the conventional class fell in the middle category at 71.28%. In conclusion, the contextual and scientific approaches have proven effective in improving students' cognitive abilities and learning independence in mathematics. Keywords: Cognitive Ability, Learning Independence, Contextual Approach, Scientific Approach